2009
DOI: 10.1007/s00572-009-0266-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of mycorrhizal susceptibility and anatomy of four palm species

Abstract: A morphological and anatomical study of the root systems of the palm species Brahea armata S. Watson, Chamaerops humilis L., Phoenix canariensis Chabaud and Phoenix dactylifera L. has been carried out to determine possible mycorrhizal colonization sites. Furthermore, the arbuscular mycorrhizal (AM) anatomical types formed by the four palm species in association with Glomus mosseae (Nicol. & Gerd.) Gerdemann & Trappe have been examined. The presence of a continuous sclerenchymatic ring in the outer cortex and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 34 publications
0
27
0
1
Order By: Relevance
“…Root anatomical features of A. alexandrae and E. edulis are evoked as one factor limiting mycorrhizal colonization. In four palm species, Dreyer et al (2010) observed the presence of a continuous sclerenchymatic ring in the outer and aerenchyma in the inner root cortex, both anatomical indicators of resistance to mycorrhizal colonization. Fischer & Jayachandran (1999) hypodermal layers.…”
Section: Discussionmentioning
confidence: 99%
“…Root anatomical features of A. alexandrae and E. edulis are evoked as one factor limiting mycorrhizal colonization. In four palm species, Dreyer et al (2010) observed the presence of a continuous sclerenchymatic ring in the outer and aerenchyma in the inner root cortex, both anatomical indicators of resistance to mycorrhizal colonization. Fischer & Jayachandran (1999) hypodermal layers.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no accompanying data have been presented on the mycorrhizal susceptibility and presence of the different AM fungal structures in these root types, although it has been repeatedly suggested that it would be highly revealing to examine root traits by root order in mycorrhizal studies (Valenzuela-Estrada et al 2008). Many studies have shown that the root orders most susceptible to being colonised are the higherorder or ultimate roots (Janos 1977;Nadarajah 1980;Fisher and Jayachandran 1999;Dreyer et al 2010). The main reason for the lack of information on the mycorrhizal susceptibility of the root orders with different root functions may be the difficulty of distinguishing them.…”
Section: Root Order Variation In Root Structure and Function And Mycomentioning
confidence: 96%
“…canariensis is characterised by a homorrhizal root system that can develop up to three root orders (Dreyer et al 2010). An abrupt change in diameter takes place with the development of each root order (Table 7.1).…”
Section: Root Morphology and Anatomymentioning
confidence: 99%
See 2 more Smart Citations